A Study of Curve Number (CN) Values in Flood-Prone Watersheds in the Flores River Basin.: Kajian Nilai Curve Number (CN) Pada Daerah Aliran Sungai (DAS) Yang Rentan Banjir Di Wilayah Sungai Flores - Krisnayanti, Denik Sri (Postgraduate Tadulako University, 2026)
Floods are natural disasters that frequently occur as a result of global climate change, land-use conversion, and human activities that damage the environment. Based on data from the 2017 Water Resources Management Pattern (PSDA) of the Flores River Basin, there are 23 flood-prone areas across 12 watersheds in the region. This study focuses on the Magepanda and Kolisia watersheds in Sikka Regency, East Nusa Tenggara, with respective areas of 61.439 km² and 32.740 km². The purpose of this research is to determine the flood discharge in both watersheds using 22 years (2003–2024) of GPM satellite rainfall data. Rainfall distribution analysis was conducted using the Normal, Log Normal, Log Pearson Type III, and Gumbel methods, while flood discharge calculations were performed using the Synthetic Unit Hydrograph (HSS) SCS-CN method through the HEC-HMS application. The results show that the peak flood discharge in the Magepanda watershed ranges from 105,8 m³/s for a 2-year return period to 793,9 m³/s for a 1000-year return period. Meanwhile, the Kolisia watershed has peak flood discharge values ranging from 68,9 m³/s for a 2-year return period to 452,6 m³/s for a 1000-year return period.